Orchestrating HIV Neutralization by Secondary Immune Response- Mediated Induction of RF Antibodies - V. Suslov, Konstantin (Current Immunology Reviews (Discontinued), 2016)
Antibody-dependent enhancement of infection is among the main challenges for HIV vaccines. Neutralization-enhancing RF antibodies (NeRFa) arising against immune complexes during secondary immune response not only enhance the action of neutralizing antibodies but also make infectionenhancing antibodies neutralizing in a sensitized virus. NeRFa represent the oldest type of immune response since it protects a fetus with unformed immune system from maternally acquired infections. Vaccination with HIV gp120 glycoprotein each 3 weeks may be a strategy to induce NeRFa both in prophylactic and therapeutic immunizations. Twenty-fold reduction in amount of protein for secondary immunization is important for an optimal induction of NeRFa. Auto-vaccination via transient immune suppression with dexamethasone might be a promising way to induce NeRFa in HIV-infected patients.
Keywords: NeRFa